الشعور بالوحدة النفسية لنازحي محافظة نينوى في المخيمات - نعمت عجاج, عدي; حاتم فضيل, ظفر (Journal of College of Education, 2020)
The importance of this research is focusing on an important segment of Iraqi society that has gone through crises and calamities Lack of security, tension and anxiety, and a threat to human safety due to bloody conflicts The fierce wars and the ensuing destruction and chaos, as the research aimed to identify a level Feeling of psychological loneliness for the displaced from Nineveh Governorate for those who live in (Barakah and Harsham) camp, according to For the variables (gender - work), the sample included (120) women who were displaced and intentionally displaced They can read and write and are aged (18) years and above, for the year (2019-2020) The two researchers used a tool to measure the feeling of psychological loneliness, consisting of (20) items Formative and virtual, as the stability of the instrument was verified by re-testing, so the stability factor was (0.83). Pearson correlation coefficient and T-test for one sample and two samples were used as statistical means. The results showed the following:- The high level of psychological loneliness among IDPs living in camps. - There is a statistically significant difference in the level of feeling the psychological unit according to the gender variable (male - female) in favor of males. - There is a statistically significant difference in the level of feeling of psychological unity according to the variable of work (working - unemployed) and in favor of the unemployed.